Stress test specific to tennis (Test): case study of an elite player - Brechbuhl, C.; Girard, O.; Millet, G. P.; Schmitt, L. (Coaching and Sport Science Review, 2016)
Although assessment of the technical, physical and physiological qualities required for performance optimisation is complex in tennis, it is nonetheless essential to training planning. While physical goals are often dissociated from technical ones, we argue that a recently validated stress test specific to tennis, known as "TEST" (Brechbuhl, Girard, Millet, & Schmitt, 2016), allows to combine both effectively. Differences in forehand and backhand efficiency may occur as a result of fatigue under standardised conditions, thus minimising emotional and tactical effects. The aim of the present case study is to offer a practical reading of TEST in an elite player.